2004
DOI: 10.1603/0046-225x-33.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Chromatic Cues During Host Location by the Pupal ParasitoidPimpla turionellae(L.) (Hymenoptera: Ichneumonidae)

Abstract: Chromatic and achromatic plant cues are expected to be particularly important for parasitoids of endophytic pupal hosts, because these stages do not feed and therefore avoid volatile emission caused by plant tissue damage. Endophytic feeding can cause discoloration or desiccation, leading to changes in color and/or brightness of infested plant parts that may be visually detected by parasitoids. The role of color cues in the host-Þnding behavior of parasitoids is poorly understood, and the visual system of most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 31 publications
0
11
0
2
Order By: Relevance
“…To find and identify their host plants, insects could use various sensory systems. A combination of visual (Bullas-Appleton et al, 2004;Fischer et al, 2004;Hausmann et al, 2004;Mäntylä et al, 2004), olfactory (Müller & Hilker, 2000;Kalberer et al, 2001;Zhang & Schlyter, 2004;Kalberer et al, 2005), and contact or gustatory cues (Jermy et al, 1988;Chapman & Sword, 1993;Mitchell, 1994;Schoonhoven et al, 1998) can finally lead the insect to its food source. However, all these cues vary in both their cost of assessment and accuracy, and some cues can be more reliable than others (Fawcett & Johnstone, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…To find and identify their host plants, insects could use various sensory systems. A combination of visual (Bullas-Appleton et al, 2004;Fischer et al, 2004;Hausmann et al, 2004;Mäntylä et al, 2004), olfactory (Müller & Hilker, 2000;Kalberer et al, 2001;Zhang & Schlyter, 2004;Kalberer et al, 2005), and contact or gustatory cues (Jermy et al, 1988;Chapman & Sword, 1993;Mitchell, 1994;Schoonhoven et al, 1998) can finally lead the insect to its food source. However, all these cues vary in both their cost of assessment and accuracy, and some cues can be more reliable than others (Fawcett & Johnstone, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, this similarity in shape may only appear to the human eye and not to the beetles, as they may even be able to use the spectral composition of the plant tissue for host plant recognition (Bullas-Appleton et al, 2004;Fischer et al, 2004;Mäntylä et al, 2004). Furthermore, the beetles may use a combination of olfactory and visual cues, which has also been found in other herbivorous insects (McIntyre & Vaughn, 1997;Cook & Neal, 1999;Strom et al, 1999;Barata & Araújo, 2001;Szentesi et al, 2002).…”
Section: Discussionmentioning
confidence: 95%
“…cucurbitae has revealed that females are particularly attracted to pigments that offer high reflectance values (white, yellow, orange) regardless of hue and, conversely, that they respond less to objects associated with low-reflecting pigments (e.g., black, blue) [26]. Some parasitoid species uses contrast (chromatic or achromatic) rather than specific color characteristics in visual host location [39]. Our findings demonstrate that visual acuity may have mediated the establishment of new host / plant relationships, ahead of olfactory adaptations.…”
Section: Discussionmentioning
confidence: 99%